Association between urinary thallium exposure and cardiovascular disease in U.S. adult population. (May 2022) - Wang, Sibo; Sun, Jiateng; Tang, Chunping; Gu, Lingfeng; Du, Chong; Wang, Hao; Ma, Yao; Wang, Liansheng
Abstract: Exposure to environmental metals, especially heavy metals, can damage human health. However, the association between metals and the prevalence of cardiovascular disease (CVD) remains controversial. The objective of this study was to determine the relationship of urinary metals to CVD in a general population of U.S. adults. We analyzed the cross-sectional data from 6867 adult (age ≥20 years) participants with 12 urinary metals in the National Health and Nutrition Examination Survey (NHANES) (2011–2016). Multivariate logistic regression and restricted cubic spline (RCS) regression were conducted to explore the association between urinary metals and CVD outcomes. Sensitivity analyses were performed to test the robustness of the results. Compared to the lowest quartile, the odds ratios with 95% confidence intervals for CVD across the quartiles were 0.73 (0.38, 1.42), 0.58 (0.42, 0.81), and 0.71 (0.59, 0.84) for urinary thallium (U–Tl) ( P for trend <0.001). RCS plot showed the nonlinear association between log2 -transformed U–Tl levels and CVD ( P for nonlinearity = 0.001). Sensitivity analyses confirmed the robustness. Higher concentrations of urinary cobalt, manganese and tungsten were associated with an increased risk of CVD. In summary, the large sample data suggests U–Tl is nonlinearly and negatively associated with the prevalence of CVD in the U.S. general adults with low exposure levels. Considering the shortcomings of cross-sectional study design, further studies are warranted to verify our results and to clarify the potential mechanisms. Graphical abstract: Image 1 Highlights: Urinary thallium was associated with cardiovascular disease. The relationship between urinary thallium and CVD was nonlinear. The association needs cautious interpretation and further research.